2015
DOI: 10.3390/s16010021
|View full text |Cite
|
Sign up to set email alerts
|

Classifier Subset Selection for the Stacked Generalization Method Applied to Emotion Recognition in Speech

Abstract: In this paper, a new supervised classification paradigm, called classifier subset selection for stacked generalization (CSS stacking), is presented to deal with speech emotion recognition. The new approach consists of an improvement of a bi-level multi-classifier system known as stacking generalization by means of an integration of an estimation of distribution algorithm (EDA) in the first layer to select the optimal subset from the standard base classifiers. The good performance of the proposed new paradigm w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 66 publications
(86 reference statements)
0
3
0
Order By: Relevance
“…The main objective of this study is to evaluate an objective method to distinguish patients and healthy people, based on language networks mapped with fMRI, and by using a machine learning (ML) approach. Previous results from a range of cognitive studies [ 21 24 ] showed successful use of ML classification. In patients with epilepsy, an ML approach based on a probabilistic regression method was used on fMRI data to evaluate the hemispheric specialization for language before surgery [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The main objective of this study is to evaluate an objective method to distinguish patients and healthy people, based on language networks mapped with fMRI, and by using a machine learning (ML) approach. Previous results from a range of cognitive studies [ 21 24 ] showed successful use of ML classification. In patients with epilepsy, an ML approach based on a probabilistic regression method was used on fMRI data to evaluate the hemispheric specialization for language before surgery [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Their results showed an average accuracy of 95.8% on the CASIA database across six emotions, which is an improvement when compared to other related studies. Álvarez et al [47] proposed a classifier subset selection (CSS) for the stacked generalization to recognize speech emotion. They used the estimation of distribution algorithm (EDA) to select optimal features from a collection of features that included eGeMAPS and SVM for classification that achieved an average accuracy of 82.45% on Emo-Db.…”
Section: Related Studiesmentioning
confidence: 99%
“…These studies focus on applying traditional image processing method to the inspection of flaws, scratches, and defects in battery separator or electrode surface. Structured light is important for visual inspection, and a novel classifier subset selection for stacked generalization is reported in [19]. In these studies, feature extraction of defects or flaws is the key to successful detection.Defect detection can be regarded as a classification problem of battery components.…”
mentioning
confidence: 99%